1993
DOI: 10.1159/000261550
|View full text |Cite
|
Sign up to set email alerts
|

Control of Calculus Formation by a Dentifrice Containing Calcium Lactate

Abstract: The aim of this study was to re-investigate the anticalculus effects of calcium lactate. To this end calcium lactate was incorporated into experimental toothpastes. Three groups of 20 human volunteers brushed their teeth at least twice daily with three different toothpastes: (1) one containing calcium lactate, (2) one containing calcium lactate plus sodium lauryl sulphate, and (3) a control toothpaste. Plaque accumulation, gingival bleeding and calculus formation were scored at the beginning and at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The combination of antigingivitis, antiplaque and antitartar technology within a single fonnulation is attractive to the general public due to the simplification which is provided in selection of toothpastes and mouthrinses for oral hygiene. Also shown in the table are reports on a number of new agent combinations tested for effects on tartar development, including a calculus solubilizmg dentifrice (citroxain; a combination of papain enzyme and citrate chelate) (186)(187), an "antiadherance" rinse (formulated with delmopinol; a surface anti-adherance agent) (200) and a calcium lactate dentifrice (192). All of these formulations were reported to have efficacy for calculus prevention.…”
Section: Tartar Control -Current Strategies For Prevention and Removamentioning
confidence: 99%
“…The combination of antigingivitis, antiplaque and antitartar technology within a single fonnulation is attractive to the general public due to the simplification which is provided in selection of toothpastes and mouthrinses for oral hygiene. Also shown in the table are reports on a number of new agent combinations tested for effects on tartar development, including a calculus solubilizmg dentifrice (citroxain; a combination of papain enzyme and citrate chelate) (186)(187), an "antiadherance" rinse (formulated with delmopinol; a surface anti-adherance agent) (200) and a calcium lactate dentifrice (192). All of these formulations were reported to have efficacy for calculus prevention.…”
Section: Tartar Control -Current Strategies For Prevention and Removamentioning
confidence: 99%
“…The product range is both SLS and alcohol free, which renders it suitable for dry mouths. Furthermore, some caries and calculus prevention is claimed through the addition of fluoride and calcium lactate, which may justify OralSeven's marketing to healthy patients as a routine toothpaste. OralSeven also boasts the inclusion of aloe vera, which has demonstrated some ability to prevent mucositis following radiation therapy .…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by studies in humans that have shown that the addition of calcium lactate to toothpastes and mouthwashes reduces calculus formation. 39,40 One limitation of the study may have been the number of cats included. In the 3-month study, the test population was divided into 2 smaller groups.…”
Section: Discussionmentioning
confidence: 99%